Potential of using host plant resistance, nitrogen and phosphorus fertilizers for reduction of Aspergillus flavus colonization and aflatoxin accumulation in maize in Tanzania - Manoza, F.S.; Mushongi, A.A.; Harvey, Jagger J.W.; Wainaina, J.; Wanjuki, I.; Ngeno, R.; Darnell, Ross; Gnonlonfin, G.J.B.; Massomo, Said M. (Elsevier, 2017)
Aflatoxin contamination (AC) in maize, caused by the fungal pathogen Aspergillus flavus(Link), starts at pre-harvest stage. Hence, interventions that reduce entry and development of A. flavus in the field are required. Trials were carried out at Seatondale and Igeri, to evaluate the effects of nitrogen and phosphorus fertilizer combinations, hereafter referred to as fertilizers, on A. flavus and AC in maize kernels. The main treatments were four combinations of N and P fertilizers (60 or 120 kg Nha−1 with 15 or 30 kg Pha−1) and sub-treatments were of six popular maize hybrids. Plants at 50% silking were inoculated with the fungus through the silk channels. Grains from inoculated and control ears were analysed for AC using Enzyme Linked Immunosorbent Assay, and pathogen content quantified by Quantitative Polymerase Chain reaction. Higher AC (mean 6.51 μg kg−1) occurred at Seatondale than Igeri (mean 0.45 μg kg−1), probably due to low temperatures (8–23 °C) at Igeri. Fertilizers didn't cause significant differences in neither pathogen colonization nor AC at both sites. However, mean A. flavusaccumulation, as measured by pathogen host DNA ratio, was thrice (0.16) as high in sub-optimal fertilizer conditions compared to optimal fertilizer rate (0.05). All hybrids were susceptible to A. flavus and AC, though a difference in AC was noted among the hybrids at both sites. PAN 691 showed the highest AC (14.68 μg kg−1), whereas UHS 5210 had the lowest AC (1.87 μg kg−1). The susceptibility varied among the hybrids and was mostly associated with ear droopiness, husk tightness, days to 50% silking, 50% pollen shed, Anthesis to silking interval, diseased ears, insect damaged ears, kernel texture, dry matter, grain filling, ear height, kernel ash content and kernel moisture content. At Seatondale, A. flavus accumulation was positively correlated with aflatoxin (r = 0.606), and both A. flavus accumulation and AC were positively correlated with diseased ears. Selection and growing of less susceptible varieties under optimal fertilizer regime offer ideal strategy for sustainable reduction of A. flavus and aflatoxin contamination in maize at pre-harvest.